Sural Nerve Size in Fibromyalgia Syndrome: Study on Variables Associated With Cross-Sectional Area - Di Carlo, Marco; Ventura, Claudio; Cesaroni, Pietro; Carotti, Marina; Giovagnoni, Andrea; Salaffi, Fausto (Frontiers in Medicine, 2020)
Increasead cross-sectional area (CSA) of sural nerve, documented by ultrasound (US), has been revealed in small fibers neuropathy, condition present in about half of patients with fibromyalgia (FM). The aims of this study were to evaluate sural nerve CSA and to establish the variables associated with increased CSA in FM patients. A cross-sectional assessment was conducted in consecutive FM patients. Demographic data, clinimetric parameters (Fibromyalgia Impact Questionnaire [FIQR]), the neuropathic pain features (PainDetect Questionnaire [PDQ]), and the sural nerve CSA were recorded. CSA was determined by US, examining the sural nerve at the lateral region of the calf. CSA was compared with demographic and clinical variables. A multiple regression analysis was conducted applying CSA as dependent variable. One hundred and ten FM patients were enrolled. Sural nerve CSA showed a significant association with body mass index (BMI) (r = 0.422; p <0.0001) and with PDQ (r = 0.361; p = 0.0001). The multiple regression analysis confirmed that BMI (p =0.0001) and PDQ (p = 0.0028) were the two independent variables associated with CSA. The severity of the disease, measured with FIQR, showed no association. An increase in sural nerve CSA is closely related to BMI and to distinctive neuropathic symptoms. Overweight and obesity appear to be associated with a FM phenotype with documented peripheral nervous system involvement. Ultrasound examination of the sural nerve at calf level may reveal useful information in patients with FM, identifying a cluster of patients with peripheral nervous system alterations. This cluster of patients is generally overweight or obese, and complains of painful symptoms with neuropathic features.